Relationship of computed tomography perfusion and positron emission tomography to tumour progression in malignant glioma. Issue 1 (16th January 2014) - Yeung, Timothy P. C.; Yartsev, Slav; Lee, Ting‐Yim; Wong, Eugene; He, Wenqing; Fisher, Barbara; VanderSpek, Lauren L.; Macdonald, David; Bauman, Glenn
Abstract Introduction This study aimed to explore the potential for computed tomography (CT) perfusion and 18‐Fluorodeoxyglucose positron emission tomography (FDG‐PET) in predicting sites of future progressive tumour on a voxel‐by‐voxel basis after radiotherapy and chemotherapy. Methods Ten patients underwent pre‐radiotherapy magnetic resonance (MR), FDG‐PET and CT perfusion near the end of radiotherapy and repeated post‐radiotherapy follow‐up MR scans. The relationships between these images and tumour progression were assessed using logistic regression. Cross‐validation with receiver operating characteristic (ROC) analysis was used to assess the value of these images in predicting sites of tumour progression. Results Pre‐radiotherapy MR‐defined gross tumour; near‐end‐of‐radiotherapy CT‐defined enhancing lesion; CT perfusion blood flow (BF), blood volume (BV) and permeability‐surface area (PS) product; FDG‐PET standard uptake value (SUV); and SUV:BF showed significant associations with tumour progression on follow‐up MR imaging (P < 0.0001). The mean sensitivity (±standard deviation), specificity and area under the ROC curve (AUC) of PS were 0.64 ± 0.15, 0.74 ± 0.07 and 0.72 ± 0.12 respectively. This mean AUC was higher than that of the pre‐radiotherapy MR‐defined gross tumour and near‐end‐of‐radiotherapy CT‐defined enhancing lesion (both AUCs = 0.6 ± 0.1, P ≤ 0.03). The multivariate model using BF, BV, PS and SUV had a mean AUC of 0.8 ± 0.1, but this was not significantly higher than the PS only model. Conclusion PS is the single best predictor of tumour progression when compared to other parameters, but voxel‐based prediction based on logistic regression had modest sensitivity and specificity.